2000
DOI: 10.1002/lt.500060122
|View full text |Cite
|
Sign up to set email alerts
|

Liver transplantation

Abstract: Liver transplantation has revolutionized the care of patients with end-stage liver disease. Liver transplantation is indicated for acute or chronic liver failure from any cause. Because there are no randomized controlled trials of liver transplantation versus no therapy, the efficacy of this surgery is best assessed by carefully comparing postoperative survival with the known natural history of the disease in question. The best examples of this are in primary biliary cirrhosis and primary sclerosing cholangiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
5

Year Published

2001
2001
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(35 citation statements)
references
References 144 publications
1
27
0
5
Order By: Relevance
“…Advances in surgical procedures and ameliorated immunosuppressive therapy have led to an extended patient and graft survival (Merion 2010;Wagner et al 2012). As a result, upper recipient age limits have been increased in the past years, and an older recipient age is not considered as a contraindication any more (Carithers 2000). In the early years of OLT, the upper age limit for recipients did not exceed 55 years (Shaw 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Advances in surgical procedures and ameliorated immunosuppressive therapy have led to an extended patient and graft survival (Merion 2010;Wagner et al 2012). As a result, upper recipient age limits have been increased in the past years, and an older recipient age is not considered as a contraindication any more (Carithers 2000). In the early years of OLT, the upper age limit for recipients did not exceed 55 years (Shaw 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Advanced age is not considered an absolute contraindication for liver transplantation (LT) (1). In the early years of LT the upper limit of age for its indication was 45-55 years (2).…”
Section: Introductionmentioning
confidence: 99%
“…The recently published American Association for the Study of Liver Diseases Practice Guidelines on Liver Transplantation concluded that OLT was indicated in carefully selected patients with HHC, but that more research was needed to determine the optimum use of OLT in these patients. 70 Because HHC is an uncommon indication for OLT, it is unlikely that meaningful conclusions can be drawn from a single-center experience. Therefore, multicenter studies that use uniform diagnostic criteria with well-defined end points are critical to further our understanding of iron overload in the setting of OLT.…”
Section: Resultsmentioning
confidence: 99%